Effectiveness and degradation pathways of bisphenol A (BPA) initiated by hydroxyl radicals and sulfate radicals in water: Initial reaction sites based on DFT prediction - Qi Han; Mingming Wang; Feiyun Sun; Boping Yu; Zijun Dong; Pu Li; Jingwen Luo; Mu Li; Xingliang Jin; Zhiguang Dai (Environmental Research, 2023)

Warming exacerbates the impact of nutrient enrichment on microbial functional potentials important to the nutrient cycling in shallow lake mesocosms - Lijuan Ren; Yuanyuan Liu; Torben L. Lauridsen; Martin Søndergaard; Boping Han; Jianjun Wang; Erik Jeppesen; Jizhong Zhou; Qinglong L. Wu (Limnology and Oceanography, 2021)
Shallow lakes, the most numerous waterbodies on Earth, are susceptible to climate warming and nutrient enrichment whose effects on the microbial functional potentials are not yet fully understood, however. Here, we applied a microarray‐based technology termed GeoChip 5.0 to investigate microbial functional genes at the beginning of April in shallow lake ecosystems simulated in mesocosms that have been undergoing nutrient enrichment and warming for 9 yr. Our results showed that warming exacerbated the impact of nutrient enrichment on microbial metabolic potentials and significantly elevated the microbial autotrophy potentials, carbon degradation potentials (e.g., starch, hemicellulose, cellulose, and chitin), and polyphosphate mobilization potentials. We also observed that warming enhanced the impacts of nutrient enrichment on microbial functional gene structure. The combination of warming and nutrient enrichment increased the deterministic effect from phytoplankton, causing higher interlinking of microbial functional genes involved in the carbon, nitrogen, phosphorus, and sulfur cycling in correlation‐based networks. Overall, we propose that the joint effect of warming and nutrient enrichment promoted the autotrophic carbon supply and the heterotrophic carbon demand and changed the carbon fluxes in the experimental mesocosms.

La(OH)3-modified magnetic sodium carboxymethyl cellulose for sequential removal of pollutants: adsorption of phosphate and subsequent photocatalytical reduction of Cr(VI) - Taiwan Liao; Pengwei Huang; Huiyu Song; Jia Guo; Xionghui Fu; Xiang Yu; Liang Peng; Boping Han; Yi Zhu; Yuanming Zhang (Environmental Science and Pollution Research, 2020)

Magnetic polymer–supported adsorbent with two functional adsorption sites for phosphate removal - Ting Li; Pengwei Huang; Taiwan Liao; Jia Guo; Xiang Yu; Boping Han; Liang Peng; Yi Zhu; Yuanming Zhang (Environmental Science and Pollution Research, 2019)

Cyanobacterial removal by a red soil-based flocculant and its effect on zooplankton: an experiment with deep enclosures in a tropical reservoir in China - Liang Peng; Lamei Lei; Lijuan Xiao; Boping Han (Environmental Science and Pollution Research, 2019)

Phytoplankton assemblages in a complex system of interconnected reservoirs: the role of water transport in dispersal - Ren Hu; Xueke Duan; Liang Peng; Boping Han; Luigi Naselli-Flores (Hydrobiologia, 2017)

Comparing biological classifications of freshwater phytoplankton: a case study from South China - Ren Hu; Boping Han; Luigi Naselli-Flores (Hydrobiologia, 2013)

Massive invasion of Arctodiaptomus dorsalis (Copepoda, Calanoida, Diaptomidae) in Philippine lakes: a threat to Asian zooplankton biodiversity? - Rey Donne S. Papa; Huiming Li; Dino T. Tordesillas; Boping Han; Henri J. Dumont (Biological Invasions, 2012)

Floating-leaved macrophyte (Trapa quadrispinosa Roxb) beds have significant effects on sediment resuspension in Lake Taihu, China - Peisheng Huang; Boping Han; Zhengwen Liu (Hydrobiologia, 2007)

Numerical study on the velocity structure around tidal fronts in the Yellow Sea - Guimei Liu; Hui Wang; Song Sun; Boping Han (Advances in Atmospheric Sciences, 2003)